2020
DOI: 10.1159/000505996
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E-Mediated Food Allergies Differ in East Mediterranean Children Aged 0–2 Years

Abstract: Objective: Precise diagnosis of allergy requires knowledge of the population's food allergy (FA) spectrum and predictors. Methods: Medical charts of Turkish children aged 0-2 years with FA and/or atopic dermatitis (AD) were reviewed. Results: A total of 1,389 patients, 912 with FA and 1,140 with AD, were included. In the FA group, the most frequently diagnosed FAs were egg white (75.9%), cow's milk (55.7%), tree nuts (31.5%) and sesame (20.6%). The detection of FA in 99% of children with any kind of FA necessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
2
21
1
Order By: Relevance
“…The spectrum of food allergies varies according to geography, lifestyle, and dietary habits. The most common classic food allergies in East Mediterranean children aged <2 years are unique to the region and include egg white, cow’s milk, tree nuts, and sesame 12 . The European Anaphylaxis Registry recorded a cohort of pediatric anaphylaxis reactions, and cow’s milk and hen’s egg were common etiologies in those aged 0‐2 years, hazelnut and cashew were common etiologies in preschool‐aged children, and peanut was a common trigger in all age‐groups 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of food allergies varies according to geography, lifestyle, and dietary habits. The most common classic food allergies in East Mediterranean children aged <2 years are unique to the region and include egg white, cow’s milk, tree nuts, and sesame 12 . The European Anaphylaxis Registry recorded a cohort of pediatric anaphylaxis reactions, and cow’s milk and hen’s egg were common etiologies in those aged 0‐2 years, hazelnut and cashew were common etiologies in preschool‐aged children, and peanut was a common trigger in all age‐groups 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In Turkish children, the foods most commonly cause food allergy were reported as egg (57.8%), cow's milk (55.9%) and hazelnut (21.9%) [10]. Kahveci et al showed that egg white, cow's milk, tree nuts and sesame were the most prevalent allergenic foods in the East Mediterranean children aged 0-24 months [11]. Kaya et al showed that OFC proven food allergy prevalence in Turkish adolescents was 0.15% and the most common food allergen was peanut followed by tree nuts [12].…”
Section: In Childrenmentioning
confidence: 99%
“…NIH (USA) news release on the above story; highlights rising concerns on lack of sesame regulation in the USA [47]. The first report from Turkey: 20.2% of food allergic children have sesame allergy [48]. The first report of an allergic reaction to sesame oil was also from the USA [28].…”
Section: Milestonementioning
confidence: 99%
“…In Lebanon, sensitization (i.e., IgE, and skin prick testing positivity) to sesame among infants, children, and adults was at 3.9%, 2.65% and 1.9%, respectively; and anaphylaxis was the only clinical symptom [37]. Later studies have identified that the sesame allergy and anaphylaxis are also a growing problem in Saudi Arabia, Iran, Kuwait, and Turkey [39,41,42,48]. Thus, the extensive use of sesame in the food and the increased reporting of sesame allergy among the Middle Eastern population suggests a strong correlation of disease with widespread exposure to sesame via the food.…”
Section: Milestonementioning
confidence: 99%